Studies of the correlation between mercury content and the content of various forms of sulfur in Polish hard coals. (1st November 2015) - Dziok, Tadeusz; Strugała, Andrzej; Rozwadowski, Andrzej; Macherzyński, Mariusz
Abstract: Similarities concerning the occurrence of mercury and sulfur in coal are the reasons for studying the correlation between mercury content and the content of the various forms of sulfur such as: total sulfur, pyritic sulfur, sulfate sulfur, and organic sulfur. For this purpose a wide range of different coals and rejects were used. Selected samples differed significantly in the content of ash, mercury, sulfur and its various forms. In the examinations, both steam and coking coals were studied. For coking coals, samples of raw coals, clean coals, middling products and rejects derived from coal preparation plants were examined. To verify the correlation a statistical analysis was performed. The Spearman's rank correlation coefficient and the correlation coefficients R for polynomial functions of degree 1 and 2 were determined. Based on the obtained results, it can be concluded, that mercury occurs in Polish hard coals both in the organic matter and the inorganic constituents. For the organic matter a significant correlation between the content of mercury and the content of total sulfur and organic sulfur was obtained for subset of examined samples characterized by a relatively low ash yield (clean coals derived from the coal cleaning process). In the case of the inorganic constituents a significant correlation between the content of mercury and the content of pyritic sulfur was obtained for the examined subset of samples characterized by a very high ash yield (rejects derived from the coal cleaning process). An analysis of the subsets of samples derived from individual mines showed that the modes of occurrence of mercury in coal were different for various Polish mines. These differences may be explained by the genetic diversity of coal i.e. various diagenetic, coalification and post-diagenetic conditions, including such phenomena as mineralization that post-dates coal formation and magmatic intrusion, etc. In order to explain the mercury and sulfur behavior in the analyzed processes of coal cleaning the percentage share of those elements in rejects in relation to raw coal was also determined. The mercury removal efficiencies recorded for the cleaning process of Polish hard coals ranged from about 33% to as much as 67%. Results of the statistical analyses did not, however, provide necessary evidence allowing for the formulation of final conclusions regarding the modes of occurrence of mercury in Polish coals, its association with sulfur present in coal as well as proportioning of mercury in the processes of coal cleaning. The results did make it possible, though, to identify the major scientific problems, which, if solved by relevant methods (e.g. XRD, SEM, EPMA), will facilitate the understanding of the Hg-modes of occurrence in various Polish hard coals. The results of the statistical analyses will also make it easier to appropriately select samples in order to explain these scientific problems.